Ideas About Groundwater in Subsurface Environments – An Investigation of College Students’ Mental Models Concerning Concepts of Physical Geography - Reinfried, Sibylle (Journal of Geography Education, 2005)
Research has established that students enter their classrooms with ideas about the natural world that do not correspond with accepted scientific findings. The diagnosis of these student preconceptions may be seen as a crucial initial step in the process of teacher-facilitated conceptual change at all grade levels which provides the basis to achieve scientific literacy. To diagnose students preconceptions teachers themselves have to be aware of their own mental models and should have an adequate comprehension of the concepts that are scientifically accepted. This paper refers to a pilot study concerning mental models of German teacher candidates about subsurface water. The topic of water was chosen because the United Nations declared 2003 the International Year of Freshwater to draw attention to the fact that water is one of the most essential resources for life and must therefore be considered an important topic in the teaching of geography. To diagnose students’ preinstructional ideas and the concepts they constructed through instruction, a group of 22 undergraduates and a group of 20 graduates were questioned using a questionnaire. Their answers were grouped in four plausible model concepts. As students’ concepts revealed erroneous assumptions and ideas, in-depth interviews were conducted with a representative subgroup to understand how these ideas were constructed. Data analysis using quantitative and qualitative methods showed that students’ mental models are partly the result of misleading illustrations presented to them in textbooks. While classroom instruction generally improved students’ concepts a small number of students clung to their naive misconceptions that seemed to persist unchanged side by side with the scientifically accepted concepts. Overall, students’ scientific knowledge about subsurface water is poor.